Perceived parental monitoring and adolescent internet addiction: A moderated mediation model. (November 2017) - Ding, Qingwen; Li, Dongping; Zhou, Yueyue; Dong, Hongning; Luo, Jinjing
Abstract: Bronfenbrenner's (1979) ecological model focuses on the interrelation between different contexts and the interaction between individuals and their proximal contexts. Based on this theory, the present study tested a moderated mediation model of family, peer, and individual characteristics to investigate how they impact adolescent Internet addiction. Specifically, we examined whether deviant peer affiliation partially mediated the relation between perceived parental monitoring and adolescent Internet addiction, and whether this indirect relation was moderated by effortful control. A total of 747 Chinese middle school students filled out anonymous questionnaires concerning perceived parental monitoring, deviant peer affiliation, effortful control, and Internet addiction. The findings indicated that while the impact of parental monitoring on Internet addiction was partially mediated by deviant peer affiliation, effortful control moderated the first stage of the indirect relationship. For low effortful control adolescents, perceived parental monitoring negatively predicted deviant peer affiliation. Conversely, the indirect path was not significant for high effortful control adolescents. These findings highlight the need to consider family, peer and individual factors simultaneously when evaluating risks associated with adolescent Internet addiction and have important implications for the prevention and intervention of adolescent Internet addiction. Highlights: Perceived parental monitoring (PPM) negatively predicted Internet addiction (IA). Deviant peer affiliation partially mediated the relation between PPA and IA. Effortful control moderated the first part of the mediation link.